1989
DOI: 10.1021/bi00446a042
|View full text |Cite
|
Sign up to set email alerts
|

Homologous membrane folate binding proteins in human placenta: cloning and sequence of a cDNA

Abstract: A preparation of folate binding protein purified from human placental membranes in the presence of a variety of protease inhibitors followed by deglycosylation with N-glycanase gave a sharp band at Mr approximately 28,000 following SDS-polyacrylamide gel electrophoresis. The deglycosylated protein bound [3H]folic acid as tightly as the native protein. Peptides obtained following digestion of the purified protein with staphylococcal V8 protease and HPLC purification were sequenced. Polyclonal antibodies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
136
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 19 publications
4
136
0
1
Order By: Relevance
“…Dideoxynucleotide sequencing of the 1.2 kb inserts from three clones resulted in a cDNA of 1230 bases that contained an identical 759-base open reading frame between bases 90 and 849 that encodes a peptide sequence of 253 amino acids ( Figure 1). The similarity between the cDNA sequences in the open reading frame of pig liver FBP and the published sequence for human placenta FBP [3] was 80 %. Back-translation of the open reading frame revealed 67-73 % similarity of the deduced pig liver FBP sequence to previously published amino acid sequences [2,3,[6][7][8]20] (Figure 2).…”
Section: Sequence Of Pig Liver Fbpmentioning
confidence: 85%
See 3 more Smart Citations
“…Dideoxynucleotide sequencing of the 1.2 kb inserts from three clones resulted in a cDNA of 1230 bases that contained an identical 759-base open reading frame between bases 90 and 849 that encodes a peptide sequence of 253 amino acids ( Figure 1). The similarity between the cDNA sequences in the open reading frame of pig liver FBP and the published sequence for human placenta FBP [3] was 80 %. Back-translation of the open reading frame revealed 67-73 % similarity of the deduced pig liver FBP sequence to previously published amino acid sequences [2,3,[6][7][8]20] (Figure 2).…”
Section: Sequence Of Pig Liver Fbpmentioning
confidence: 85%
“…The similarity between the cDNA sequences in the open reading frame of pig liver FBP and the published sequence for human placenta FBP [3] was 80 %. Back-translation of the open reading frame revealed 67-73 % similarity of the deduced pig liver FBP sequence to previously published amino acid sequences [2,3,[6][7][8]20] (Figure 2). The deduced amino acid sequence revealed cross-species conservation of 16 cysteine sites, 11 tryp-…”
Section: Sequence Of Pig Liver Fbpmentioning
confidence: 85%
See 2 more Smart Citations
“…Folates bound to FBP are incorporated into cells by means of endocytosis (Kamen et al, 1988;Anderson et al, 1992). Four isoforms of folate receptors (␣ ␤, ␥, and ␦) have been cloned in human (Elwood, 1989;Ratnam et al, 1989;Shen et al, 1994;Spiegelstein et al, 2000), whereas three isoforms of FBPs (1, 2, and 3) have been identified in mice (Brigle et al, 1991;Spiegelstein et al, 2000). RFC has a relatively low affinity for folate, whereas a larger amount of folate is transported into cells by this protein (Sirotnak and Tolner, 1999).…”
Section: Introductionmentioning
confidence: 99%